2022
DOI: 10.3390/en15197093
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Renewable Energy Development: Evidence from the EU Countries

Abstract: Sustainable development of the global economy can be achieved with the help of renewable energy (RE). The paper investigates the determinants of RE development in order to boost its adoption. The determinants of RE deployment were analyzed using random-effects GLS regression for the panel data from 27 EU member states in 2011–2020.The results confirm that economic development and high employment in advanced technology manufacturing are drivers of the RE sector, whereas unemployment growth affects RE deployment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…The present study has both limitations and strengths. It did not assess significant variables like secondary income, economic growth 61 , energy use per capita 62 , political participation, and economic freedom 63 . Furthermore, this study relied on secondary data, making it difficult to establish a cause-and-effect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has both limitations and strengths. It did not assess significant variables like secondary income, economic growth 61 , energy use per capita 62 , political participation, and economic freedom 63 . Furthermore, this study relied on secondary data, making it difficult to establish a cause-and-effect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Tu et al [19] undertook a study on 27 EU countries to discover the determinants of renewable energy supply. The study's results revealed that advanced technology, economic growth, political participation, and geographic location influence renewable energy supply.…”
Section: Determinants Of Renewable Energy Supplymentioning
confidence: 99%
“…In general, the study of various determinants of renewable energy development is principally for its qualitative analysis and forecasting [31]. Using the example of European countries, a group of scientists [32][33][34] studied the critical determinants of renewable energy and clean energy technologies as prospects for transforming the region's energy industry. The cumulative value of renewable energy for society as a whole is considered in work [35], and in work [36], a group of researchers focuses directly on the economic difficulties of Nigerians in solving energy supply issues.…”
Section: Literature Reviewmentioning
confidence: 99%